2017
DOI: 10.1016/j.jcmgh.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Evidence Linking Helicobacter pylori to Gastric Cancer

Abstract: Gastric cancer has long been recognized to be accompanied and preceded by chronic gastritis, lasting decades. Arguably, the most important development in our understanding of gastric cancer pathogenesis over the past 50 years has been the realization that, for most cases of gastric cancer, Helicobacter pylori is the cause of the underlying gastritis. Gastritis can promote gastric carcinogenesis, typically via the Correa cascade of atrophic gastritis, intestinal metaplasia, and dysplasia. Nested case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
166
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(201 citation statements)
references
References 66 publications
(69 reference statements)
1
166
0
21
Order By: Relevance
“…Among clinical risk factors for GC, which include smoking, high-salt diet, high intake of meats, and bile reflux, infection with H pylori is a leading factor, especially in distal GC 18, 19, 20, 21. On the basis of improved estimates from prospective studies, 89% of new non-cardia GC cases are attributable to H pylori worldwide 22 …”
Section: Etiologic Factors In Gastric Carcinogenesismentioning
confidence: 99%
“…Among clinical risk factors for GC, which include smoking, high-salt diet, high intake of meats, and bile reflux, infection with H pylori is a leading factor, especially in distal GC 18, 19, 20, 21. On the basis of improved estimates from prospective studies, 89% of new non-cardia GC cases are attributable to H pylori worldwide 22 …”
Section: Etiologic Factors In Gastric Carcinogenesismentioning
confidence: 99%
“…Entre los factores de riesgo clínicos para el CG se incluyen: tabaquismo, dieta rica en sal, alta ingesta de carnes, reflujo biliar e infección por H. pylori [7][8][9][10] . La mayoría de los cánceres no cardiales son atribuibles al H. pylori 11 .…”
Section: Factores Etiologicosunclassified
“…Thus far, most but not all studies, systematic reviews and meta-analysis confirmed (Lin et al, 1995) that H. pylori is associated with gastric cancer. However, due to conflicting reports (Moss, 2017) in the literature regarding the relationship between H. pylori and human gastric cancer Helicobacter pylori is still not accepted as the cause of gastric cancer (Barukčić, 2005;Barukčić, 2009;Ando et al, 2006).…”
Section: Introductionmentioning
confidence: 99%